Pengaruh Brand Image, Promosi Media Sosial dan Electronic Word of Mouth (E-Wom) Terhadap Keputusan Pembelian Produk Ceramella Sunscreen The Originote Pada Pengguna Tokopedia - Sari, Lita Adhitya; Mubarok, Dadan Abdul Aziz (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
The beauty world is currently an industry that is in great demand by young and adult populations, so many companies can produce domestic beauty brands that can compete with foreign brands. Using skin care products is one of Indonesian women's most popular trends. Products that assist keep skin healthy and shield it from too much sun exposure are known as skin care products. The Originote brand, Ceramella Sunscreen the Originote, is one of the brands that is presently in competitionThis study sought to ascertain whether Tokopedia users' purchases of Ceramella Sunscreen The Originote products were influenced by brand image, social media advertising, and electronic word-of-mouth. This study takes a descriptive and exploratory approach while using a quantitative research methodology. The study's population consisted of all 138,800 Originote brand followers on the Tokopedia marketplace. One hundred respondents made up the sample, and a Google Form with a Likert scale was utilized to collect the data. The study's findings show that while the t-test and electronic word-of-mouth do not significantly influence consumers' decisions to buy Ceramella Sunscreen The Originote products, the brand image and social media promotion of these products have a positive and significant partial impact. Brand image, social media advertising, and electronic word-of-mouth all significantly influence purchasing decisions, either simultaneously or through the f test.